Platinum-hydrogen vibrations and low energy electronic excitations of 13-atom Pt nanoclusters - Keppeler, Melanie; Roduner, Emil (Physical chemistry chemical physics : PCCP, 2014)
Two Pt-H vibrational bands at 1679 cm(-1) and 1392 cm(-1) observed with 13-atom Pt clusters supported in LTL zeolite by Fourier Transform Infrared (FTIR) spectroscopy confirms that H atoms bridge two Pt atoms across the edges of the metal cluster. An additional broad absorption band centred near 2200 cm(-1) which exhibits some substructure is assigned to low energy electronic excitations across the HOMO-LUMO gap of the developing band structure of the nanocluster.